2019
DOI: 10.26623/themessenger.v11i1a.818
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Attitudes Towards Web Advertising: An Evidence from Malaysia

Abstract: <p><em>The purpose of this study is to examine the factors which influence of the consumer’s Attitudes Towards Web Advertisement (ATWA). Drawing conceptual framework from Elaboration Likelihood Model (ELM), the influence of the six independent variables have been analyzed in this study, including informativeness, entertainment, credibility, economic value, interactivity, and materialism. The data has been obtained from 384 Honda users by using online questionnaires. Results of multiple regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Numerous studies (e.g. Rahimi et al, 2019;Hanaysha & Momani, 2021;Lang et al, 2022) have reported a positive relationship of advertisement informativeness with brand loyalty. For example, Rahimi et al (2019) conducted a study in Malaysia investigating the relationship of advertisement informativeness of auto brands on social media with brand loyalty.…”
Section: Self-brand Connection As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies (e.g. Rahimi et al, 2019;Hanaysha & Momani, 2021;Lang et al, 2022) have reported a positive relationship of advertisement informativeness with brand loyalty. For example, Rahimi et al (2019) conducted a study in Malaysia investigating the relationship of advertisement informativeness of auto brands on social media with brand loyalty.…”
Section: Self-brand Connection As a Mediatormentioning
confidence: 99%
“…Rahimi et al, 2019;Hanaysha & Momani, 2021;Lang et al, 2022) have reported a positive relationship of advertisement informativeness with brand loyalty. For example, Rahimi et al (2019) conducted a study in Malaysia investigating the relationship of advertisement informativeness of auto brands on social media with brand loyalty. The authors investigated the advertisement informativeness of the Honda car brand on social media platforms and they reported a positive relationship of advertisement informativeness with brand loyalty.…”
Section: Self-brand Connection As a Mediatormentioning
confidence: 99%
“…They proved, that there was a significant relationship between interactivity and intention (Liao et al, 2019) (Tan et al, 2018) (Alalwan, 2018). Interactivity is also an important factor in advertising through the web, because it affects consumer attitudes towards web advertising (Rahimi et al, 2019).…”
Section: Introductionmentioning
confidence: 96%